PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PADA MASYARAKAT - Tubagus Ahmad Darojat (Indonesian Journal of Basic Education, 2019)
This type of research uses explanatory models that combine quantitative and qualitative research models. In collecting data using observation techniques, study documents, questionnaires and interview techniques. Data analysis uses relative frequency distribution analysis. The results of this study indicate that in general the application of the principles of good governance in services to: (1) improving the quality of services to the community; (2) To continue to improve, so as to be able to serve the community well, service to the community continues to be maintained